Preparing for a Global Community. Achieving an International Perspective in Higher Education - Pickert, Sarah M.; ERIC Clearinghouse on Higher Education; George Washington Univ., Washington, DC. School of Education and Human Development (Washington, DC : ERIC Clearinghouse on Higher Education, 1992)
This brief report summarizes a longer document with the same title. The report discusses the response of colleges and universities in the United States to the needs of graduate students to become equipped to make personal and and public policy decisions as citizens of an international society. It notes that curriculum changes in higher education are showing greater enhancements of the international experience in the classroom and a tightening of foreign language standards. Federal spending in undergraduate study abroad has also increased substantially, as well as the U.S. commitment to working with the Economic Community and the United Nations Educational, Scientific, and Cultural Organization to standardize educational credential reporting, licensing, and certification. Steps that faculty and administrators can take in this environment include widening the curriculum to expose students to other cultures, widening opportunities for international contact, and evaluating organizational structures that help or hinder international activities. Contains six references. (GLR)
Availability: Publications Department, ASHE-ERIC Higher Education Reports, The George Washington University, One Dupont Circle, Suite 630, Washington, DC 20036-1186 (
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RI88062014.
ERIC Note: For the full length report, see HE 025 868.
Administrators.
Practitioners.
Keywords: College Administration; College Faculty; College Second Language Programs; Cultural Awareness; Curriculum Development; Educational Objectives; Educational Planning; Exchange Programs; Foreign Culture; Foreign Students; Higher Education; International Education; Multicultural Education; Student Mobility; Study Abroad; Undergraduate Study; ERIC Digests; ERIC Publications; Reports, General; ERIC Digests in Full Text